2020
DOI: 10.1016/j.wneu.2020.05.246
|View full text |Cite
|
Sign up to set email alerts
|

An Exit Strategy for Resuming Nonemergency Neurosurgery after Severe Acute Respiratory Syndrome Coronavirus 2: A United Kingdom Perspective

Abstract: Substantial healthcare resources have been diverted to manage the effects of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic, and nonemergency neurosurgery has been effectively closed. As we begin to emerge from the crisis, we will need to manage the backlog of nonemergency neurosurgical patients whose treatment has been delayed and remain responsive to further possible surges of SARS-CoV-2 infections.-METHODS: In the present study, we aimed to identify the core themes and challenges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…They determined four criteria that should be fulfilled prior to resuming elective neurosurgical procedures: (1) structured prioritization of neurosurgical cases; (2) decreased incidence of COVID-19 infection; (3) adequate testing of all elective neurosurgical patients; (4) coordination of strategy at individual and organizational levels. 43…”
Section: Neurosurgical Practicementioning
confidence: 99%
“…They determined four criteria that should be fulfilled prior to resuming elective neurosurgical procedures: (1) structured prioritization of neurosurgical cases; (2) decreased incidence of COVID-19 infection; (3) adequate testing of all elective neurosurgical patients; (4) coordination of strategy at individual and organizational levels. 43…”
Section: Neurosurgical Practicementioning
confidence: 99%
“…15 In China, 3.8% (n = 1716 of 44,672) of COVID-19 cases occurred in healthcare personnel, 14.8% (n = 254) of which were severe; in Lombardy, Italy, 20% of the cases occurred in healthcare work-ers. 16,17 Subsequent reports suggested that the first nosocomial spread event occurred during pituitary surgery in which 14 people were exposed and infected in China. 18…”
Section: Staff Operational Changesmentioning
confidence: 99%
“…34 During the preoperative period, a thoracic CT scan and nucleic acid sequencing (reverse-transcription polymerase chain reaction [RT-PCR]) are performed for the preliminary diagnosis of COVID-19; however, the chances of a false-negative test result have been reported to be as high as 16.7%. 17 Patients with positive results are identified as having confirmed COVID-19, and patients with prelimi-nary negative results are considered suspect for having COVID-19. Therefore, various levels of protection and specific adaptations to operating rooms occur in a negative pressure environment with access routes specifically designated for all suspect or confirmed cases.…”
Section: Preoperative Managementmentioning
confidence: 99%
“… 3 Regarding hospital operations specifically, institutional exit strategies such as that proposed by Hill et al. 4 for resuming nonemergency neurosurgical operations will likely prove crucial in gradually moving toward prepandemic caseloads and maintaining the necessary precautions required to ensure both patient and hospital staff safety. Although such guidelines will most likely vary between different institutions, the common themes that have been consistently described in reported studies have included ensuring the availability of personal protective equipment for healthcare workers, continuing the use of telemedicine within neurosurgical workflows, and working to balance the increased surgical demand with the available hospital resources.…”
mentioning
confidence: 99%
“…Although such guidelines will most likely vary between different institutions, the common themes that have been consistently described in reported studies have included ensuring the availability of personal protective equipment for healthcare workers, continuing the use of telemedicine within neurosurgical workflows, and working to balance the increased surgical demand with the available hospital resources. 4 , 5 , 6 , 7 , 8 , 9 As pandemic restrictions are eased and surgical volumes increase, it will also be important to identify those patients requiring urgent neurosurgical intervention. Guides for prioritizing neurosurgery cases, such as that proposed by Thomas et al., 10 using the Delphi method, will likely become increasingly important as surgeons aim to clear the case backlogs that have accumulated during the height of the pandemic.…”
mentioning
confidence: 99%